Drought dynamics on the Mongolian steppe, 1970-2006 - Sternberg, T.; Thomas, D.; Middleton, N. (International Journal of Climatology, 2011)
Drought is an ongoing feature in Mongolia's steppe environment, yet it remains poorly documented. Awareness of drought conditions is important in the countryside because 50% of the rural population derive their livelihood from climate-dependent pastoralism. In this study, precipitation records, 1970-2006, from five meteorological stations in three steppe provinces were analysed using the Standard Precipitation Index to identify drought events at 1-, 3-, 5- and 17-month timescales. Results found that the probability of drought occurrence in the steppe was slightly less than expected and that the occurrence, intensity and duration were site-specific characteristics. Additionally, its distribution was neither spatially consistent nor uniform over time at different sites. The most serious drought, in terms of severity and duration, was in progress in 2006 at the end of the study.